Isolated oligohydramnios and long-term neurological morbidity of the offspring. (22nd December 2020) - Dorot, Avital; Wainstock, Tamar; Sheiner, Eyal; Walfisch, Asnat; Landau, Daniella; Harlev, Avi
Abstract: This study aimed to assess the association between maternal-isolated oligohydramnios (IO) and offspring long-term neurological complications. A population-based retrospective cohort study was conducted, including all births at a single tertiary medical center in Israel between the years 1991 and 2014. Multiple pregnancies and potential pregnancy complications associated with oligohydramnios were excluded. The computerized obstetrical database was linked with the computerized dataset of all pediatric hospitalizations of the same medical center. Evaluation of cumulative neurological-associated hospitalizations rate over time was compared using a Kaplan–Meier survival curve. The Weibull survival parametric model was conducted to assess the neurological-associated hospitalization risk in the presence of IO, while accounting for potential confounders. A total of 190, 259 pregnancies were included in the study, of which 4063 (2.13%) pregnancies were complicated with IO. Total neurological-related hospitalizations were significantly more common in the IO group (3.7% in the IO group and 3.0% in the comparison group, p  = 0.005). Pervasive developmental disorder, movement disorders, developmental disorders, and degenerative and demyelization disorders were all specific neurological diagnoses significantly more common in the exposed group. The survival curve demonstrated a significantly higher cumulative hospitalization rate in the exposed group (log-rank p = 0.001). Using a multivariate model adjusting for gestational age, maternal age, and labor induction, an independent association between IO and long-term neurological morbidity of the offspring was observed (adjusted hazard ratio 1.203; 95% CI 1.02–1.42). In summary, a significant association was found between pregnancies complicated by IO and long-term neurological morbidity of the offspring.